Effect of web-enhanced learning activities on the English achievement of freshmen at Nueva Vizcaya General Comprehensive High School - Bustos, Katherine Faith M. (Transactions of the National Academy of Science and Technology, 2011)
The study established the effecta of Web-Enhanced Learning Activities (WELA) on the achievement of English of freshmen students of Nueva Vizcaya General Comprehensive High School (NVGCHS). The research combined the quantitative approach using quasi-experimental design, with the qualitative approach involving immersion learning among 66 students from two first year classes, 34 under the experimental group and 32 under the control group. Observation, participation in the classroom interaction, and interview were employed. The study covered the third grading period of School Year 2007-2008. The achievement level of respondents was evaluated based on pretest and posttest, significantly outperforming the students in the control group. Moreover, based on data from interview and classroom observation, the following positive behaviors among the students under the WELA : (a)increased intearaction among the students, between the students and learning materials, and between the students and the teacher; (b)decreased cases of absenteeism; (c)independent learning; (d)enhanced and structured learning styles; and (e)more defined focus in learning. Administrators should encourage their teachers to be involved in updating their teaching and learning methods and stategies. Teachers should to be more open to new techniques and styles; and join trainings, seminars, and workshop on web-enhanced learning and ICT integration.